"But it is not so among you" : echoes of power in Mark 10.32-45 - De Mingo Kaminouchi, Alberto (Journal for the study of the New Testament. Supplement series, 2003)
Power is an issue that is attracting increased interest among philosophers, theologians and social scientists. The gospel of Mark, especially in 10:32-45, contains teachings attributed to Jesus about the use and abuse of power. This book applies a combination of different methods and approaches: mainly orality, criticism, literary criticism and a sensitivity for the social and cultural environment of the text, showing the centrality of Jesus's message on the issue of power both for the plot and for the theology of Mark. This message is a call to practice leadership in a way that is subversive.